The Influence of Brand Equity on Consumer Buying Behavior - Shrestha, Arpan; Pun, Lal Bahadur (Kshitiz Management Review, 2026)
The current study explores the influence of brand equity on consumer behavior related to the purchase of electronic products in Nepal. Building brand equity is increasingly critical for organizations in today’s highly competitive environment to lure consumers. This study seeks to investigate the role of four aspects of brand equity including brand awareness, brand association, brand loyalty, and perceived quality on consumer buying behavior. A descriptive and causal research design was used and quantitative data were collected using structured questionnaires from 585 online buyers of electronic products in Nepal through stratified random sampling method. Collected data were analyzed using statistical software such as JAMOVI through various methods such as descriptive statistics, correlation, and regression. Reliability and validity of measurement scales were tested using Cronbach’s Alpha, Composite Reliability (CR), Average Variance Extracted (AVE) and HTMT to confirm that they have acceptable reliability and validity. It has been found that all four constructs of brand equity significantly positively influence consumer buying behavior of electronic products in Nepal. Perceived quality was observed to be the strongest predictor followed by brand association, brand loyalty and brand awareness. It was also observed from correlation test that all variables are moderately positively correlated with each other. It can be concluded that consumer buying behavior of electronic products in Nepal is greatly influenced by their perceptions about quality of the products, associations and loyalty towards brands.